"We don't have students colour maps anymore …" a survey of social studies teachers use of visual materials. Issue 3 (2nd October 2017) - Brugar, Kristy A.
Abstract: Many researchers, teacher educators, teachers and students view graphics in text as an aspect of student learning (e.g. engagement, comprehension). However, as a field we have not addressed teachers' pedagogical content knowledge and decision-making associated with the use of graphics, student learning and issues of access. This mixed methods study is an exploration of K-12 teachers' uses of visuals materials (e.g. artifacts, graphs, maps and photographs). Social studies teachers ( n = 87) from across the United States completed a survey in which each respondent documented the ways in which they did or did not use visuals in their classrooms. Teachers described photographs and maps complementing their lecture material as well as in-depth student analysis of images to demonstrate their understanding of a time and place. However, none of the respondents described instruction about they ways to engage with visual material. This work contributes to the knowledge on social studies teaching and teacher instructional choices.